Judicial Law-Making and the Limits of Constitutional Adjudication: Reassessing Judicial Power in Indonesia after Decision No. 92/PUU-XXII/2024 - Winda Wahyuni; Multi Sri Asnani; Dirawati (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This article examines the implications of Constitutional Court Decision No. 92/PUU-XXII/2024 for the limits of judicial authority and Indonesia’s constitutional design. The decision not only reviews the constitutionality of Article 118(e) of the Village Law but also formulates an operational norm through conditional interpretation, signaling a functional shift of the Court from its classical role as a negative legislator toward judicial law-making. Employing a doctrinal legal approach with conceptual analysis and limited comparison, the study analyzes the decision, relevant legislation, and constitutional theory literature using qualitative content analysis within the theoretical frameworks of Hans Kelsen, Alec Stone Sweet, Ran Hirschl, and Mark Tushnet. The findings demonstrate that the Court’s normative intervention operates as a corrective mechanism to address legal uncertainty and to protect constitutional rights, while simultaneously generating structural tensions with the principles of separation of powers and democratic accountability. The article argues that the normalization of the Court’s role as a positive legislator risks incrementally altering the institutional balance without sufficient democratic legitimacy. The study’s main contribution lies in integrating national doctrinal analysis with global constitutional debates on the limits of judicial law-making in constitutional democracies, particularly in developing countries with unstable legislative dynamics.